The caudal bursa in the Heligmonellidae (Nematoda: Trichostrongylina): Characterization and hypothesis on its evolution - Durette Desset, M. C. (2012)
The different patterns of the caudal bursa of the Heligmonellidae (Nematoda) are redefined, taking into account the grouping of rays 2-6 and the sequence of origin of these rays from their common trunk. The type of symmetry of the caudal bursa is also redefined. The following patterns were observed and characterized: the basic patterns: types 2-3, 2-2-1, 1-3-1 and 1-4 and the intermediary patterns: type 2-3 tending to type 2-2-1, type 2-2-1 tending to type 1-3-1, type 1-3-1 tending to type 1-4 and type 2-2-1 tending to type 1-4. An evolutionary interpretation of the patterns is attempted and seems to follow the direction: 2-3 to 2-2-1 to 1-3-1 to 1-4. Seven atypical patterns are described. The caudal bursae were classified based on their symmetry: subsymmetrical, dissymmetrical and asymmetrical. Independently of the type of symmetry, the two latero-ventral lobes may have the same or different patterns. The type of symmetry, the ratio between the two latero-ventral lobes and a characteristic pattern were utilized to characterize the caudal bursae at the level of the genus and the subfamily. The combination of the right/left ratio and the type of symmetry gives heterogeneous results, with no real association between these characters. The most conspicuous asymmetries and dissymmetries were found among the Nippostrongylinae. The most frequent pattern in the Heligmonellidae is the basic type 2-2-1; types 1-3-1 and 1-4 are less frequent but are characteristic of several genera; type 1-4 is absent from the Heligmonellinae. Whatever the pattern, in the Heligmonellidae rays 4 and 5 are the last to diverge from the common trunk of rays 2-6.